Long-term persistence of immunity after hepatitis B vaccination: Is this substantiated by the literature? - Terence T. Lao (Taylor & Francis Group, 2017)
Hepatitis B vaccination is held to provide life-long protection against hepatitis B virus (HBV) infection, but evidence for this notion remains wanting, since no studies have assessed the vaccinees in their fourth decade of life. Indeed, there are several reports indicating that despite vaccination in infancy, the prevalence of HBV infection still increased with age in the vaccinees, and that both anti-HBs titer and anamnestic response declined with age. Clearly it is time to clarify the long-term protection conferred by vaccination in infancy, and to implement remedial measures such as booster doses of vaccine in subjects without immunoprotection.